1998
DOI: 10.1037/0735-7036.112.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons' (Columba livia) encoding of geometric and featural properties of a spatial environment.

Abstract: Pigeons (Columba livia) searched for hidden food in a rectangular environment constructed to eliminate external orientation cues. A feature group was initially trained with distinct features in each corner. A geometric group was initially trained with no featural information. Tests revealed that both groups encoded the geometry of the apparatus. The geometric group was then retrained with features, and a series of tests was administered to both groups. Transformation tests revealed that the groups differed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
214
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(246 citation statements)
references
References 19 publications
32
214
0
Order By: Relevance
“…This result supports and extends previous studies showing that encoding of geometric information is not overshadowed by the featural cues (e.g., Hayward, McGregor, Good, & Pearce, 2003;Kelly et al, 1998;Vallortigara et al, 1990). Previous studies have shown that several animals, including humans, will readily encode the geometric properties of a 3-D environment (e.g., humans: Hermer & Spelke, 1994birds: Kelly et al, 1998;Vallortigara et al, 1990;and fish: Sovrano et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…This result supports and extends previous studies showing that encoding of geometric information is not overshadowed by the featural cues (e.g., Hayward, McGregor, Good, & Pearce, 2003;Kelly et al, 1998;Vallortigara et al, 1990). Previous studies have shown that several animals, including humans, will readily encode the geometric properties of a 3-D environment (e.g., humans: Hermer & Spelke, 1994birds: Kelly et al, 1998;Vallortigara et al, 1990;and fish: Sovrano et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…This effect has also been revealed in a rectangular arena with pigeons (Kelly, Spetch, and Heth, 1998). Other studies have shown with rats (Cheng, 1986), goldfish (Sovrano, Bisazza, & Vallortigara, 2003), chicks (Tommasi & Vallortigara, 2003) and monkeys (Gouteux, Thinus--Blanc, & Vauclair, 2001) that the presence of a landmark does not prevent animals making use of geometric cues to find a hidden goal.…”
mentioning
confidence: 69%
“…the colour of a wall) in order to reorient themselves [e.g. Wsh: redtail splitWns (Xenotoca eiseni): Sovrano et al 2002Sovrano et al , 2003goldWsh (Carassius auratus) : Vargas et al 2004; birds: chicks (Gallus gallus): Vallortigara et al 1990Vallortigara et al , 2004pigeons (Columba livia) : Kelly et al 1998;Vargas et al 2004a;mammals: rhesus monkeys: Gouteux et al 2001;tamarins: Deipolyi et al 2001]. Interestingly, however, a "primacy" of geometric information seems to be apparent in spatial reorientation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, a "primacy" of geometric information seems to be apparent in spatial reorientation. When animals are trained in the presence of conspicuous local, non-geometric cues, such as panels located at the corners of a rectangular enclosure, and subsequently tested after removal of these featural cues, their behaviour usually reveals that spontaneous encoding of geometric information has occurred, in spite of the fact that featural information alone suYced for spatial reorientation during training (chicks: Vallortigara et al 1990; pigeons: Kelly et al 1998;Wsh: Sovrano et al 2003).…”
Section: Introductionmentioning
confidence: 99%